2006
DOI: 10.1038/sj.onc.1209571
|View full text |Cite
|
Sign up to set email alerts
|

ELAC2, a putative prostate cancer susceptibility gene product, potentiates TGF-β/Smad-induced growth arrest of prostate cells

Abstract: Transforming growth factor-b (TGF-b) elicits a potent growth inhibitory effect on many normal cells by binding to specific serine/threonine kinase receptors and activating specific Smad proteins, which regulate the expression of cell cycle genes, including the p21 cyclin-dependent kinase (CDK) inhibitor gene. Interestingly, cancer cells are often insensitive to the anti-mitogenic effects of TGF-b for which the molecular mechanisms are not well understood. In this study, we found that the candidate prostate can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 44 publications
(57 reference statements)
1
42
0
1
Order By: Relevance
“…In another study, human ELAC2/RNase Z L was shown to participate in the TGF-b/Smad-signaling pathway acting as a scaffold protein recruiting transcription factors and regulating growth arrest of prostate cells (Noda et al, 2006).…”
Section: Drnasez Is a Metabolic Enzyme With Multiple Dutiesmentioning
confidence: 98%
See 1 more Smart Citation
“…In another study, human ELAC2/RNase Z L was shown to participate in the TGF-b/Smad-signaling pathway acting as a scaffold protein recruiting transcription factors and regulating growth arrest of prostate cells (Noda et al, 2006).…”
Section: Drnasez Is a Metabolic Enzyme With Multiple Dutiesmentioning
confidence: 98%
“…Apparently, the efficiencies of both the sgRNA/RNase Z L and the canonical RISC-based pathways of gene silencing are quite comparable. Another mechanism of gene regulatory function was proposed for RNase Z L in the TGF-b/Smad-signaling pathway that inhibits growth of prostate cells (Noda et al, 2006). Even though RNase Z L itself does not possess transcriptional or DNA binding activities, it can act as a scaffold protein recruiting transcription factors to the TGF-b induced promoters.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer cells, particularly those of the breast, elevate their expression of inactive LIP C/EBPβ variants, which uncouples TGF-β from regulation Myc and p15 expression and correlates with metastatic disease development [112]. Along these lines, ELAC2 recently was identified as a transcriptional co-factor that mediates p21 expression in conjunction with Smad2:FAST-1 complexes in prostate epithelial cells [113]. Importantly, loss of ELAC2 in developing and progressing prostate cancers inactivates their ability to undergo growth arrest in response to TGF-β [114].…”
Section: Tgf-β and Dysregulated Cell Proliferationmentioning
confidence: 99%
“…Plasmid Construction-Constitutively active activin receptor-like kinase 5 (ALK5ca)/V5, FLAG-Smad2, FLAG-Smad3, FLAG-Smad4, (CAGA) 12 -luc, FLAG-Smad2⌬exon3, HA-TCF7L2, HA-TCF7L2⌬ , and HA-␤-catenin were described previously (22)(23)(24)(25)(26). Myc-TCF7L2 was kindly gifted by Dr. Watanabe (27).…”
Section: Methodsmentioning
confidence: 99%